Biorealistic Control of Hand Prosthesis Augments Functional Performance of Individuals With Amputation - Luo, Qi; Niu, Chuanxin M.; Chou, Chih-Hong; Liang, Wenyuan; Deng, Xiaoqian; Hao, Manzhao; Lan, Ning (Frontiers in Neuroscience, 2021)
Human hand has compliant properties arising from muscle biomechanics and neural reflexes, which is absent in conventional prosthetic hands. We recently proved the feasibility to restore neuromuscular reflex control (NRC) to prosthetic hand using real-time computing neuromorphic chips. Here we show that restored NRC augments ability of individuals with forearm amputation to complete grasping tasks, including standard box and blocks test (BBT), golf balls test (GBT) and potato chips test (PCT). The latter two were more challenging, but novel to prosthesis tests. Performance of a biorealistic controller (BC) with restored NRC was compared to that of a proportional linear feedback (PLF) controller. Eleven individuals with forearm amputation were divided into two groups: one with experience of myocontrol of a prosthetic hand and another without any. Controller performances were evaluated by success rate, failure (drop/break) rate in each grasping task. In controller property tests, biorealistic control achieved a better compliant property with a 23.2% wider range of stiffness adjustment than that of PLF control. In functional grasping tests, participants could control prosthetic hand more rapidly and steadily with neuromuscular reflex. For participants with myocontrol experience, biorealistic control yielded 20.4%, 39.4%, and 195.2% improvements in BBT, GBT and PCT respectively compared to PLF control. Interestingly, greater improvements were achieved by participants without any myocontrol experience for BBT, GBT and PCT at 27.4%, 48.9%, 344.3% respectively. The functional gain of biorealistic control over conventional control was more dramatic in more difficult grasp tasks of GBT and PCT, demonstrating the advantage of neuromuscular reflex control. Results support the hypothesis that restoring neuromuscular reflex in hand prosthesis can improve neural motor compatibility to human sensorimotor system, hence enabling individuals with amputation to perform delicate grasps that are not tested with conventional prosthetic hands.